Analysis of Trademark Cancellation Due to Bad Faith and Substantial Similarity to a Well-Known Mark (A Case Study of Supreme Court Decision Number 836 K/Pdt.Sus-HKI/2022) - Islamiati Haris, Dian (JURNAL MAHASISWA YUSTISI, 2025)
This research analyzes the legal aspects of trademark cancellation due to bad faith and substantial similarity to a well-known mark. The case study reviewed is Supreme Court Decision Number 836 K/Pdt.Sus-HKI/2022 between Starbucks Corporation and PT Sumatra Tobacco Trading Company. The objective of this study is to identify the criteria for determining a well-known trademark and examine how the court assessed elements of bad faith in trademark registration. Using normative-empirical legal research methods and a case approach, this study finds that the Supreme Court affirms the importance of protecting well-known trademarks by applying the principles set out in Law No. 20 of 2016 and international conventions. This case sets a legal precedent that strengthens legal certainty and fairness in trademark protection.